Endoscopic Ligation of Esophageal Varices (EVL) Compared with Endoscopic Injection Sclerotherapy (EIS) - Ülkü SARITAŞ; Uğur YILMAZ; Bülent YILDIRIM; Burhan ŞAHİN (Turkish Journal of Gastroenterology, 2020)
-